Phosphorylation of MafA Is Essential for Its Transcriptional and Biological Properties - Benkhelifa, Sofia (American Society for Microbiology, 2001)
We previously described the identification of quail MafA, a novel transcription factor of the Maf bZIP (basic region leucine zipper) family, expressed in the differentiating neuroretina (NR). In the present study, we provide the first evidence that MafA is phosphorylated and that its biological properties strongly rely upon phosphorylation of serines 14 and 65, two residues located in the transcriptional activating domain within a consensus for phosphorylation by mitogen-activated protein kinases and which are conserved among Maf proteins. These residues are phosphorylated by ERK2 but not by p38, JNK, and ERK5 in vitro. However, the contribution of the MEK/ERK pathway to MafA phosphorylation in vivo appears to be moderate, implicating another kinase. The integrity of serine 14 and serine 65 residues is required for transcriptional activity, since their mutation into alanine severely impairs MafA capacity to activate transcription. Furthermore, we show that the MafA S14A/S65A mutant displays reduced capacity to induce expression of QR1, an NR-specific target of Maf proteins. Likewise, the integrity of serines 14 and 65 is essential for the MafA ability to stimulate expression of crystallin genes in NR cells and to induce NR-to-lens transdifferentiation. Thus, the MafA capacity to induce differentiation programs is dependent on its phosphorylation.